Pelindung yang Menyandung: Menelisik Politik Emosi Kasus Persekusi Mahasiswa Katolik di Tangerang Selatan - Setyowati, Temi (ARUMBAE: Jurnal Ilmiah Teologi dan Studi Agama, 2024)
Emotional politics can be an effective strategy to build support or steer public opinion. It can also create polarization and cause social instability if manipulated irresponsibly. Emotional politics is one of the tools rulers use to achieve their goals in terms of weakening or intimidating other parties. The utilization of emotional politics was carried out by unscrupulous authorities, such as the Head of RT, in the case of persecution of Pamulang University students, South Tangerang, who were praying the Rosary in their boarding house. By collecting secondary data from various literature related to the case, This study uses a literature study approach by conducting a literature review to analyze the emotional politics of the authorities mobilizing citizens' emotions to intimidate minority groups. The results showed that religious harmony within the neighborhood association (RT) is still ‘homework’ for the pluralistic Indonesian nation. The practice of intolerance followed by verbal and physical violence is still an issue of human rights violations in the context of an Indonesian state based on Pancasila.